Examining Additive and Synergistic Relations Between Preschool Self-Regulation and Executive Function Skills: Predictions to Academic Outcomes - Finders, Jennifer K.; Duncan, Robert J.; Korucu, Irem; Bryant, Lindsey B.; Purpura, David J.; Schmitt, Sara A. (Frontiers in Psychology, 2021)
In the present study, we examined the extent to which teacher-rated self-regulation and directly assessed executive function skills were independently, additively, or synergistically related to academic achievement during the transition to kindergarten. The sample included 126 children (42% female; M age = 4.73 years) from families with low incomes who participated in a larger evaluation of state-funded preschool. Regression models with children nested in their respective preschool classrooms investigated main effects and moderated effects of teacher-rated self-regulation skills manifested in preschool classroom behaviors and cognitive executive function skills assessed through direct assessments on math, literacy, and vocabulary in the spring of preschool and in the fall of kindergarten. Results revealed independent but not additive relations between executive function and math in the spring of preschool and self-regulation and literacy in the fall of kindergarten. One significant interaction emerged providing evidence for synergistic relations between teacher-rated self-regulation and directly assessed executive function for literacy at both timepoints across the transition to kindergarten. Implications for policy and practice are discussed.